Efficacy and safety of transcranial pulse stimulation in young adolescents with attention-deficit/hyperactivity disorder: a pilot, randomized, double-blind, sham-controlled trial - Cheung, Teris; Yee, Benjamin K.; Chau, Bolton; Lam, Joyce Yuen Ting; Fong, Kwan Hin; Lo, Herman; Li, Tim Man Ho; Li, Albert Martin; Sun, Lei; Beisteiner, Roland; Cheng, Calvin Pak Wing (Frontiers in Neurology, 2024)
Background: This is the first study to evaluate the efficacy and safety of transcranial pulse stimulation (TPS) for the treatment of attention-deficit/hyperactivity disorder (ADHD) among young adolescents in Hong Kong. Methods: This double-blind, randomized, sham-controlled trial included a TPS group and a sham TPS group, encompassing a total of 30 subjects aged 12–17 years who were diagnosed with ADHD. Baseline measurements SNAP-IV, ADHD RS-IV, CGI and executive functions (Stroop tests, Digit Span) and post-TPS evaluation were collected. Both groups were assessed at baseline, immediately after intervention, and at 1-month and 3-month follow-ups. Repeated-measures ANOVAs were used to analyse data. Results: The TPS group exhibited a 30% reduction in the mean SNAP-IV score at postintervention that was maintained at 1- and 3-month follow-ups. Conclusion: TPS is an effective and safe adjunct treatment for the clinical management of ADHD. Clinical Trial Registration: ClinicalTrials.gov, NCT05422274.